Perlindungan Perempuan dari Pemaksaan Perkawinan Perspektif Maqashid Syari’ah (Studi Fatwa Kupi Ke-2 No. 06/MK-Kupi-2/XI/2022) - Ilya, Ivada (Fakultas Syariah INSURI Ponorogo, 2023)
Forced marriages that still occur in Indonesia are triggered by various factors, ranging from customs to religious reasons. The religious argument used to justify forced marriage is the right of the guardian's ijbar. Male guardians have the right of ijbar to marry off their children or those under their guardianship. This became the basis for the Women's Ulama Congress Discussion Forum (KUPI) in one of its deliberations to declare that the protection of women from forced marriage is mandatory. This research is a literature study in which the fatwa of KUPI (Indonesian Women's Ulama Congress) on marriage coercion becomes the object of research. the focus of the research is the relationship between the kupi fatwa and the classical fiqh text on mujbir guardians and then analysed using Jamaluddin Athiyah's maqashid sharia theory. The results of this study show that Islam does not necessarily give the guardian the opportunity to freely marry his child. There are several rules and conditions that must be met by the guardian. These conditions must be fulfilled in exercising the right of consent and must not be violated by the guardian, including the absence of mudharat to the child to be married off. KUPI's fatwa on the protection of women from forced marriage aims to prevent mischief and misfortune that occurs to women. By using the perspective of maqashid shari'ah Jamaluddin Athiyah, the protection of women from forced marriage is in line with the concept of maqashid shari'ah Jamaluddin Athiyah.